2011 IEEE Biomedical Circuits and Systems Conference (BioCAS) 2011
DOI: 10.1109/biocas.2011.6107772
|View full text |Cite
|
Sign up to set email alerts
|

New subdural electrode contacts for intracerebral electroencephalographic recordings: Comparative studies on neural signal recording in vivo

Abstract: In this paper, we propose new subdural electrode contacts to improve signal-to-noise ratio (SNR) for intracerebral electroencephalographic (icEEG) recording. We describe the proposed electrodes material composition, fabrication process, electro-chemical impedance spectroscopy analyses, and in vitro comparative studies with commercial electrodes (microelectrodes -MRE, depth electrodes -DPE, and subdural electrodes -SDE). The proposed subdural electrode contacts are made of Platinum (Pt) or Gold (Au). Compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The study of epileptic seizure detection and analysis has been carried out with both scalp EEG recordings (EEG) and intracranial EEG recordings (iEEG). Scalp EEG recordings use electrodes placed on the surface of the head at equal distance with the 10-20 system as the most commonly used configuration [20,33]. The iEEG signals use intracranial electrodes placed inside the skull when the clinical, structural and functional data are obtained before implantation to locate the epileptogenicity region in the brain [22].…”
Section: Data Acquisition and Eeg Databasementioning
confidence: 99%
“…The study of epileptic seizure detection and analysis has been carried out with both scalp EEG recordings (EEG) and intracranial EEG recordings (iEEG). Scalp EEG recordings use electrodes placed on the surface of the head at equal distance with the 10-20 system as the most commonly used configuration [20,33]. The iEEG signals use intracranial electrodes placed inside the skull when the clinical, structural and functional data are obtained before implantation to locate the epileptogenicity region in the brain [22].…”
Section: Data Acquisition and Eeg Databasementioning
confidence: 99%
“…We have previously shown that pure platinum (Pt) or pure Au electrodes provided higher conductivity than commercial electrodes. 22 Therefore, contacts of the mini-grid electrodes are made of pure Pt or Au, and wire connections between the electrodes (thickness, 0.05 mm) and amplifiers are made using the same materials used for electrodes but with 0.1 mm diameter wires.…”
Section: Proposed Novel Intracranial Recording Systemmentioning
confidence: 99%
“…We have studied the fundamentals facts for these false detections. Primary requirement for a seizure detector is to analyze high quality icEEG recording so that noise does not degrade detection performance [6]. To do so, we increase conductivity of electrodes and wired path in order to improve signal-to-noise ratio [6].…”
Section: Epilepsy Seizure Onset Detectionmentioning
confidence: 99%
“…Primary requirement for a seizure detector is to analyze high quality icEEG recording so that noise does not degrade detection performance [6]. To do so, we increase conductivity of electrodes and wired path in order to improve signal-to-noise ratio [6]. Secondly, we have analyzed electrographic seizure onset of many patients and found optimize detection criteria [1], [4], [5].…”
Section: Epilepsy Seizure Onset Detectionmentioning
confidence: 99%